iPhone SDK 3 programming advanced mobile development for Apple iPhone and iPod touch - Ali, Maher; Safari eBooks (Chichester, West Sussex, U.K. : J. Wiley & Sons, 2009)
"iPhone SDK 3 Programming shows you how to build great applications for the iPhone and iPod Touch. Inside, veteran mobile developer and Bell Labs scientist Maher Ali begins with a foundational introduction to Objective-C and Cocoa programming, and then guides you through building programs with Apple's iPhone SDK 3"--Resource description page.
Description based on print version record.
Includes index.
Keywords: iPhone (Smartphone) -- Programming; iPod touch (Digital music player); Cell phones -- Programming; Mobile computing; Electronic books